Weed dynamics, production potential and economics of sorghum [Sorghum bicolor (L.) Moench] cultivars as influenced by weed management practices - Jat, A.L.; Massey, J.X.; Nepalia, V.; Joshi, Ekta (Annals of Agricultural Research, 2016)
A field experiment was undertaken at Udaipur (Rajasthan) to evaluate the effect of weed management practices on weed dynamics, production potential and economics of sorghum [(Sorghum bicolor L.) Moench] cultivars during kharif 2010. Results showed that the intercropping with cowpea + one hand weeding (HW) has recorded lesser density and their dry matter accumulation at harvest of all types of monocots, dicots and total weeds as compared to other treatments. On other hand, other than weed free treatment, intercropping with cowpea + 1 HW recorded maximum grain, stover and biological yields and also net returns and B/C ratio. The corresponding increases in grain, stover and biological yield due to intercropping with cowpea + 1 HW were of the order of 84.7, 17.1 and 29.5 per cent over weedy check. Among sorghum cultivars, CSH 16 gave higher grain yield, net returns and B/C ratio while CSV 20 recorded higher stover and biological yield. Maximum weed control efficiency and minimum weed index were obtained under intercropping with cowpea + 1 HW.